Effects of Fatigue in Lower Back Muscles on Basketball Jump Shots and Landings. Issue 1 (5th December 2022) - Lin, Hui-Ting; Kuo, Wen-Chieh; Chen, Yo; Lo, Tang-Yun; Li, Yen-I; Chang, Jia-Hao
Introduction: The aim of this study was to explore effects of fatigue in lower back muscles on the performance of countermovement jumps (CMJ), jump shots (JS) and landing impact. Methods: Twelve male healthy collegiate basketball players (age: 22.8 ± 2.7 yrs, stature: 178.0 ± 5.1 cm, body mass: 74.5 ± 6.8 kg) volunteered to participate in this study. Data were collected utilizing a 3D motion analysis system, force plate, and surface electromyography. Field-goal percentage, the lowest point of the center of mass (CoM), the angles of joints during taking off phase and landing, and the electromyography parameters of the rectus femoris, erector spinae lumbalis, and of the lower limbs when performing CMJ and JS were recorded. Lower back muscle fatigue intervention was introduced and followed by a post-test to explore the effects of fatigue in the lower back muscles. Statistical analysis was performed using paired-samples t -test. Results: After lower back muscle fatigue, field-goal percentages dropped, and lowest point of CoM was increased during JS. Ankle plantar flexion of the hopping leg during CMJ and JS increased, and their knee flexion angles of the hopping leg were reduced when landing. CMJ and JS changed the contribution ratio of both legs after low back fatigue. Conclusions: Temporary low back muscles fatigue decreased the athletes' performance and causes a change in landing strategy.